2009
DOI: 10.1063/1.3213621
|View full text |Cite
|
Sign up to set email alerts
|

The design and application of an in-laboratory diffraction-enhanced x-ray imaging instrument

Abstract: We describe the design and application of a new in-laboratory diffraction-enhanced x-ray imaging (DEXI) instrument that uses a nonsynchrotron, conventional x-ray source to image the internal structure of an object. In the work presented here, a human cadaveric thumb is used as a test-sample to demonstrate the imaging capability of our instrument. A 22 keV monochromatic x-ray beam is prepared using a mismatched, two-crystal monochromator; a silicon analyzer crystal is placed in a parallel crystal geometry with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 37 publications
0
35
0
1
Order By: Relevance
“…Comparing single-distance PBI and single rocking-angle DEI of mouse and rabbit lungs indicates that DEI yields images of superior contrast than those for PBI, and both techniques show a significant contrast improvement over conventional absorption radiographs (11). The use of DEI with laboratory sources suffers from low monochromatic flux and the resulting long exposure times, which are not compatible with in vivo imaging applications (21,22).…”
mentioning
confidence: 94%
“…Comparing single-distance PBI and single rocking-angle DEI of mouse and rabbit lungs indicates that DEI yields images of superior contrast than those for PBI, and both techniques show a significant contrast improvement over conventional absorption radiographs (11). The use of DEI with laboratory sources suffers from low monochromatic flux and the resulting long exposure times, which are not compatible with in vivo imaging applications (21,22).…”
mentioning
confidence: 94%
“…Kitchen et al [9] and Khelashvili et al [10] showed that the origin of the angular spreading of the X-ray beam was multiple-refractions of the beam. Of utmost importance to the clinical translation of DEI, Parham et al [11 ‱‱ ] and Nesch et al [12] have shown that DEI contrast is maintained when an X-ray tube source is used, and Deimoz et al have demonstrated that DEI has enhanced signal-to-noise ratio (SNR) compared to gratingbased PCI when imaging at higher X-ray energies [13]. Mammography DEI's enhanced soft tissue contrast is of particular importance in mammography.…”
Section: Proof-of-principle Dei Studiesmentioning
confidence: 99%
“…Two competing approaches to X-ray tube-based DEI have been proposed and pre-clinical prototypes of these systems have been reported by Parham et al [11 ‱‱ ] and Nesch et al [12]. Parham's DEI system utilizes symmetric crystals to generate a slot X-ray beam DEI system while Nesch's system utilizes asymmetric crystals to produce an area X-ray beam.…”
Section: Clinical Translation Of Deimentioning
confidence: 99%
“…23,24 Analyzer-based imaging has mostly been performed using a synchrotron light source, but is being developed for use with X-ray tube sources. 25 …”
Section: Introductionmentioning
confidence: 99%